Clinical comparison of one recovered case and one fatal case of human infection with H7N9 avian influenza in Shanghai Public Health Clinical Center in China - ZHENG, Yufang (Penerbit Universiti Sains Malaysia, 2013)
H7N9 avian influenza is the latest subtype of influenza virus to emerge in the world. By April 17, 2013 in Shanghai, a total of 31 confirmed cases were reported, and 11 of these patients died. The epidemiological characteristics and the clinical progress of this new human flu infection are still not clear. Thirteen confirmed patients have now been treated in Shanghai Public Health Clinical Center. Among the first batch of patients, hospitalised at the beginning of April 2013, two who were admitted with the same estimated date of onset of disease had very different outcomes. After active treatment at the Centre, one recovered by April 18, 2013, but one patient entered critical condition and died on April 11, 2013. The clinical and laboratory characteristics in hospital are here analysed and compared to learn more about H7N9 avian influenza. Confirmation that the observed differences are valuable for prognosis and treatment decisions for H7N9 patients awaits authentication by analysis of more patients.